ANALYTICAL HIERARCHY PROCESS APPROACH ON CUSTOMER REVISIT INTENTION OF CAFÉ AND BAR AT KAWASAN MEGAMAS MANADO (STUDY ON CABAL O’REILLYS, REPLAY) - Kumontoy, Nadiya P.; Saerang, David P. E.; Arie, Fitty V. (Universitas Sam Ratulangi, 2021)
A growing number of cafes in Manado accompanied by hanging out culture which is becoming increasingly common among young people nowadays becomes an interesting phenomenon. Café and bar are typically present in most urban and suburban areas. One of the area at Manado is at Kawasan Megamas Manado. Revisit intention is a factors that makes the café or restaurant keep their customer and make the café or restaurant last for a long time. There’s some factor that can affect the customer revisit intention, such as cleanliness, food quality, price, service quality, store atmosphere, and variety of product. The aim of this study is to know the most important criteria for to drive the customer revisit intention and the most preferred Café and Bar at Kawasan Megamas Manado. This research used analytical hierarchy process with sample of 60 respondents. The result shows based on six criteria (cleanliness, food quality, price, service quality, store atmosphere and variety of menu), there are top three criteria that has the most influence for customer. For the most preferred Café and Bar, Replay become the most customer revisit intention to café and bar in Manado City. Every cafe and bar in Manado needs to pay attention seriously toward these factors. Customer will seek a clean place, good atmosphere of the café and bar, and also with an affordable price. Keywords: consumer revisit intention, cleanliness, food quality, price, service quality, store atmosphere, variety of product.